SOSIALISASI DAN PELATIHAN PENANGGULANGAN PEMADAM KEBAKARAN DI DESA SEBAUNG KECAMATAN GENDING - Husni Mubaroq; Dedi Joko Hermawan; Venny Maulidah Perdani; Kristiyono Kristiyono (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The increasing density of housing in rural areas has heightened the risk of fires, often exacerbated by delayed information, traffic congestion, limited water sources, and inaccessible locations. To address this issue, a socialization program was conducted in Sebaung Village to enhance community knowledge and skills in fire prevention and management. Activities included education sessions and practical simulations using both traditional and modern methods, such as fire extinguishers. The results showed improved community understanding of fire causes, firefighting techniques, and preventive measures. Residents now better understand the fire process based on three main elements and the importance of preparing simple tools, such as sand, burlap sacks, towels, and blankets, as preventive measures.